PERGESERAN DAN KONFIGURASI POLITIK HASIL PILEG 2019: KAJIAN DAN ANALISIS TERHADAP DINAMIKA POLITIK DI SULAWESI SELATAN - Jurdi, Syarifuddin (Jurnal Politik Profetik, 2019)
Elections are a means of popular sovereignty, through the Election the elite leaders will be selected through democratic elections. 2019 Simultaneous Election is the first election that unites the president-vice presidential election with the legislative election, the election results show a friction and exchange of positions between the ruling elite. Based on the results of the 2019 elections in South Sulawesi, there was a shift in the position of the elite, out of a total of 85 members of the South Sulawesi Provincial DPRD, 59 people were newcomers (first elected as members of the Provincial DPRD), only 26 incumbents were still elected. This shift in position was caused by increased political awareness of citizens, also influenced by the practice of clientelism and patronage. A number of elected elites were candidates who were not too firmly rooted, nor were elites who stand out in the community, but the "X" factor that lead a number of candidates to the DPRD of South Sulawesi province. Among the elected elites there were a number of names that were family or relatives of the ruling elite, for example the son of the Regent of Bone was elected as a member of the provincial DPRD, the son of a DPRD RI member from PPP was also thought to have been elected, because of his father's influence.